Republic of Armenia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2008)
This Selected Issues paper for the Republic of Armenia shows that building up fiscal space during economic expansions is crucial for the effective implementation of stimulatory policies during downturns. Armenia's tax revenue remains one of the lowest in the region, and significantly below potential. The legislative changes introducing a VAT threshold and a simplified regime for those businesses below the threshold, as well as the adoption of a comprehensive and ambitious modernization plan for revamping tax administration, are promising steps in the right direction.